Gamifying Portuguese Language Learning: A Case Study Examining a Quest-Based Website to Prompt Oral Production and Interaction in Learners of Portuguese L2 - Carla Cristina Munhoz Xavier (Revista Brasileira de Linguística Aplicada, 2020)
ABSTRACT One of the major challenges when teaching second language learners is to maintain them motivated and eager to learn and work on the proposed activity. The literature showed that a combination of social constructivism and technology-integrated learning is crucial for achieving the goals set by modern educational objectives. However, in order to have a robust response from students, one should take into account the psychological aspect of intrinsic and extrinsic motivation. This paper proposes a gamified activity in Portuguese L2 that aims to intensify the students’ motivation. Ten undergraduate students participated in this study. Their responses show that novel studies based on awards and gamification can boost the students’ motivation when learning Portuguese.